2018
DOI: 10.1515/jib-2018-0054
|View full text |Cite
|
Sign up to set email alerts
|

Search for New Candidate Genes Involved in the Comorbidity of Asthma and Hypertension Based on Automatic Analysis of Scientific Literature

Abstract: Comorbid states of diseases significantly complicate diagnosis and treatment. Molecular mechanisms of comorbid states of asthma and hypertension are still poorly understood. Prioritization is a way for identifying genes involved in complex phenotypic traits. Existing methods of prioritization consider genetic, expression and evolutionary data, molecular-genetic networks and other. In the case of molecular-genetic networks, as a rule, protein-protein interactions and KEGG networks are used. ANDSystem allows rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…CD40LG is a cytokine that binds to CD40, a type II transmembrane protein that belongs to the tumor necrosis factor (TNF) gene superfamily [ 47 ]. CD40LG has been reported to be associated with the development of asthma [ 48 , 49 ]. Lee et al indicated that CD40LG which interacted with CD86 involved in the development of Allergic Asthma [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD40LG is a cytokine that binds to CD40, a type II transmembrane protein that belongs to the tumor necrosis factor (TNF) gene superfamily [ 47 ]. CD40LG has been reported to be associated with the development of asthma [ 48 , 49 ]. Lee et al indicated that CD40LG which interacted with CD86 involved in the development of Allergic Asthma [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…C-X-C motif chemokine 10 (CXCL10) is a small cytokine belonging to the CXC chemokine family that is correlated and responsible for the greater susceptibility of patients with severe portal hypertension, diabetes, obesity, and lung cancer [ 101 104 ]. Interleukin 1 alpha (IL1A) is a member of the interleukin 1 cytokine family that is involved in the molecular mechanisms of hypertension, diabetes, obesity, and lung cancer [ 88 , 105 107 ]. Interferon regulatory factor 7 (IRF7) is a member of the interferon regulatory transcription factor family and is involved in the pathogenesis of diabetes, obesity, and lung cancer [ 108 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…the STAT3 gene encodes the STAT family transcription factor mediating the cellular responses to interleukins and regulates the inflammatory response [ 45 , 46 ];…”
Section: Discussionmentioning
confidence: 99%
“…TBX21, TBX5 кодируют белки -факторы активации транскрипции, экспрессия этих факторов снижена в T-клетках дыхательных путей больных астмой [16,44]; STAT6 кодирует фактор активации транскрипции семейства STAT; экспрессия этого гена значительно повышена у больных тяжелой формой БА [16]; ген STAT3 кодирует фактор активации транскрипции семейства STAT, который опосредует клеточные ответы на интерлейкины и действует как регулятор воспалительного ответа [45,46]; STAT4 кодирует фактор активации транскрипции семейства STAT, экспрессия этого гена снижена у больных БА [47];…”
Section: Discussionunclassified